Increased Serological Response Against Human Herpesvirus 6A Is Associated With Risk for Multiple Sclerosis - Engdahl, Elin; Gustafsson, Rasmus; Huang, Jesse; Biström, Martin; Lima Bomfim, Izaura; Stridh, Pernilla; Khademi, Mohsen; Brenner, Nicole; Butt, Julia; Michel, Angelika; Jons, Daniel; Hortlund, Maria; et al. (Frontiers in Immunology, 2019)
Human herpesvirus (HHV)-6A or HHV-6B involvement in multiple sclerosis (MS) etiology has remained controversial mainly due to the lack of serological methods that can distinguish the two viruses. A novel multiplex serological assay measuring IgG reactivity against the immediate-early protein 1 from HHV-6A (IE1A) and HHV-6B (IE1B) was used in a MS cohort (8742 persons with MS and 7215 matched controls), and a pre-MS cohort (478 individuals and 476 matched controls) to investigate this further. The IgG response against IE1A was positively associated with MS (OR = 1.55, p = 9x10-22), and increased risk of future MS (OR = 2.22, p = 2x10-5). An interaction was observed between IE1A and Epstein-Barr virus (EBV) antibody responses for MS risk (attributable proportion = 0.24, p = 6x10-6). In contrast, the IgG response against IE1B was negatively associated with MS (OR = 0.74, p = 6x10-11). The association did not differ between MS subtypes or vary with severity of disease. The genetic control of HHV-6A/B antibody responses were located to the HLA region and the strongest association for IE1A was the DRB1*13:01-DQA1*01:03-DQB1*06:03 haplotype while the main association for IE1B was DRB1*13:02-DQA1*01:02-DQB1*06:04. In conclusion a role for HHV-6A in MS etiology is supported by an increased serological response against HHV-6A IE1 protein, an interaction with EBV, and an association to HLA genes.